MODEL OPTIMASI PENJADWALAN PRODUKSI YANG TERINTEGRASI DENGAN MEMPERTIMBANGKAN FAKTOR BIAYA - Enty Nur Hayati (Jurnal Ilmiah Dinamika Teknik, 2010)
This handing out study model of optimal scheduling of integrated production to cover determination of allocation activity of production, arrangement of operations of process of job shop and planning of capacities as  integrated activity. Criterion the used is to fulfill order a number of product that happened at number of period from an planning horizon as a mean to total cost minimization. Keywords: Production Allocation, Scheduling of Shop Job, Planning of Capacities, Product Structure of Multi-Level.